PERILAKU DISIPLIN ANAK USIA 5-6 TAHUN DALAM KEGIATAN PEMBELAJARAN DARING DI RUMAH PADA MASA PANDEMI - Wintari, Anak Agung Raka Sri; Risina, Duana Fera (Prodi PG-PAUD, FKIP, Universitas Trilogi, 2022)
This study was conducted with the aim of “Describe the disciplined behavior of children aged 5-6 years in online learning activities at home during the pandemic at Pertiwi Abhilasa Kindergarten School, Jl. Daksinapati Timur Raya No.10, RT.7/RW.14, Rawamangun, Kec. Pulo Gadung, East Jakarta City, Special Capital Region of Jakarta 13220” using qualitative descriptive research methods. The subjects of this study were all students in TK B class at TK Pertiwi Abhilasa, Jl. Daksinapati Timur Raya No.10, RT.7/RW.14, Rawamangun, Kec. Pulo Gadung, East Jakarta City, Special Capital Region of Jakarta 13220. The number of students in TK B Pertiwi Abhilasa class in the 2020/2021 school year is 15 children, consisting of 7 boys and 8 girls. Data collection techniques used in the form of observation, interviews and documentation with the guarantor of the validity of the data carried out using triangulation techniques. The results obtained are the disciplined behavior of children aged 5-6 years in online learning activities at home during the pandemic through three indicators, namely: the presence of children, children's participation in online learning activities, and the ethics and manners of children in participating in online learning activities, already seen in the children of TK B Pertiwi Abhilasa class.